Absolutely continuous spectrum of a typical operator on a cylinder. Issue 3 (17th February 2017) - Safronov, Oleg
Abstract : We consider a family of elliptic operators depending on a real parameter and prove that the a.c. spectrum covers the half-line for almost every value of .